Stigma towards tuberculosis: psychometric validation of an instrument for its measurement - Upegui-Arango, Luz Dary (2019)
Introduction. The stigma towards tuberculosis affects the search for timely medical care and adherence to treatment for fear of family, social or institutional rejection. Objective. To validate an instrument to measure the stigma towards tuberculosis applying Rasch methodology. Methods. Cross-sectional study. The analysis was based on the aspects suggested by Messick and operationalized by Wolfe and Smith with Rasch methodology; the dichotomous model was used, where adjustment estimates of the items, coherence in the measure, separation and reliability indices, invariance, unidimensionality and the person-item relation were evaluated. Results. 250 people were interviewed, 195 without tuberculosis and 55 with tuberculosis. Thirty-five items were evaluated, of which 10 were excluded for showing mismatches and differential functioning of the item. Twenty-five valid